A typology of user liability to IT addiction. (2nd March 2016) - Vaghefi, Isaac; Lapointe, Liette; Boudreau‐Pinsonneault, Camille
Abstract: To date, information systems (IS) research mainly has provided a monolithic view of information technology (IT) use, considering it to be a desired behaviour with positive outcomes. However, given the dramatic increase in the use of technology during the last few years, susceptibility to IT addiction is increasingly becoming an important issue for technology users and IS researchers. In this paper, we report the results of a study that focuses on identifying variations in user liability to IT addiction, which reflects the susceptibility of individual users to develop IT addiction. First, a review of the literature in different disciplines (e.g. health, psychology and IS) allows us to better understand the concepts of IT addiction and liability to addiction. The literature review also provides an overview of the antecedents and consequences associated with IT addiction. Then, building on the analysis of 15 in‐depth interviews and 182 exploratory open‐ended surveys collected from smartphone users, we apply the concept of liability to addiction in the IT use context and propose a typological theory of user liability to IT addiction. Our typology reveals five ideal types; each can be associated to a user profile ( addict, fanatic, highly engaged, regular and thoughtful ). Building upon both the extant literature and our results, we put forth propositions to extend the theoretical contributions of the study. We finally discuss the contributions and implications of our paper for research and practice.